Idiosomal setae in the family Phytoseiidae (Acari: Mesostigmata): variation, geographical distribution and taxonomic considerations. (4th June 2014) - Tixier, Marie‐Stéphane; Kreiter, Serge
<x xml:space="preserve">Abstract</x> Phytoseiidae classification is based on idiosoma chaetotaxy and the assumed evolutionary process is seta suppression. This article aims to determine how depilation could have taken place depending on seta position, subfamily and region. For this, the occurrence of 21 variable setae on dorsal and ventral shields was determined for 1996 species in seven biogeographical regions. The occurrence of eight rare setae assumed to be past relics and 11 rarely absent setae (assumed to be undergoing a loss process) was analysed. The subfamily Phytoseiinae has 'lost' the highest number of primitive setae, the subfamily Amblyseiinae has 'retained' the highest number and Typhlodrominae has an intermediate position, except for the seta z6. The subfamily Phytoseiinae shows the highest number of setae undergoing a loss process, whereas the subfamily Typhlodrominae has lost these setae in 674 species and subfamily Amblyseiinae in 415 species, making this latter subfamily that with the most retained dorsal setae. According to spatial seta occurrence, it could be hypothesized that Amblyseiinae originated from South Gondwana, Typhlodrominae from the Euro‐America region (Laurasia zone) and Phytoseiinae from the Ethiopian area. The presently admitted classification of Phytoseiidae is discussed with regard to the occurrence of rarely present setae (assumed to have been lost in high frequency). © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 112, 606–624.